From Smelly Buildings to the Scented Past: An Overview of Olfactory Heritage - Bembibre, Cecilia; Strlič, Matija (Frontiers in Psychology, 2022)
Olfactory heritage is an aspect of cultural heritage concerning the smells that are meaningful to a community due to their connections with significant places, practices, objects or traditions. Knowledge in this field is produced at the intersection of history, heritage science, chemistry, archaeology, anthropology, art history, sensory science, olfactory museology, sensory geography and other domains. Drawing on perspectives from system dynamics, an approach which focuses on how parts of a system and their relationships result in the collective behaviours of the system, we will outline a series of practices relevant to this field and identify the elements, materials and competences involved, as well as the connections and interactions. While promising research on olfactory heritage is growing, much of the knowledge that could advance our understanding of this field is still being developed within disciplinary boundaries, leading to little integration of the knowledge and methods and limited interdisciplinary interpretation of findings. In the first part, we review the methodologies for identifying, researching and preserving olfactory heritage, highlighting methodological opportunities and challenges from diverse perspectives like smellscape research, odour nuisance management or heritage science. In the second part, we review the presentation and communication of olfactory heritage in museums and other heritage spaces, outlining the value of presenting scents to wide audiences for interpretation and engagement purposes. Finally, we discuss challenges associated with historic scent reconstruction, and discuss future directions for the field, such as the potential of mining large digital collections for olfactory data.